2019
DOI: 10.1136/bjophthalmol-2018-313470
|View full text |Cite
|
Sign up to set email alerts
|

Modified Goldmann prism intraocular pressure measurement accuracy and correlation to corneal biomechanical metrics: multicentre randomised clinical trial

Abstract: PurposeClinically evaluate intraocular pressure (IOP) measurements taken with a Goldmann applanation tonometer (GAT) prism and a modified surface Goldmann prism examining measurement differences correlated to central corneal thickness (CCT) and corneal hysteresis (CH) values.DesignProspective, open-label, randomised, controlled, multicentre reference device accuracy analysis.MethodsA GAT and a modified surface GAT prism measured IOP on 243 unique eyes. The study design and methodology complied with Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…In the attempt to find a reliable method in measuring the IOP after CRS, several devices have been tested, such as pneumotonometer, Tono Pen (TP), non-contact tonometer (NCT), such as TonoPachymeter, dynamic contour tonometer (DCT), Ocular Response Analyzer (ORA), Corvis ST and CATS Tonometer and only the last four has been proven to be as reliable as GAT. [42][43][44][45][46][47][48][49][50][51][52] Schipper, 26 to rehabilitate the GAT, in 2000 suggested to measure the IOP with GAT and TP in the corneal periphery because they found a higher IOP of 1.8-2.3 mmHg in the corneal periphery compared to the values measured in the central corneal region.…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to find a reliable method in measuring the IOP after CRS, several devices have been tested, such as pneumotonometer, Tono Pen (TP), non-contact tonometer (NCT), such as TonoPachymeter, dynamic contour tonometer (DCT), Ocular Response Analyzer (ORA), Corvis ST and CATS Tonometer and only the last four has been proven to be as reliable as GAT. [42][43][44][45][46][47][48][49][50][51][52] Schipper, 26 to rehabilitate the GAT, in 2000 suggested to measure the IOP with GAT and TP in the corneal periphery because they found a higher IOP of 1.8-2.3 mmHg in the corneal periphery compared to the values measured in the central corneal region.…”
Section: Discussionmentioning
confidence: 99%
“…The 72 eye sample size was calculated using the difference between two paired means with an α=0.05 (2-tailed), β=0.2, power=0.85 and the mean differences and standard deviations from previous studies. 20,22,25 The following exclusionary conditions were prevented from study participation: corneal scarring, lid, corneal, or ocular conditions, disease, disorders, or infection that potentially affect corneal biomechanics and may have confounded the study results. Also excluded from the study were high myopes (>6 diopters) and high astigmatism (>3 diopters).…”
Section: Description Of Study Populationmentioning
confidence: 99%
“…(Figure 1) Several studies, including intracameral pressure comparisons, have shown the CATS prism to have significantly decreased sensitivity to variations in corneal biomechanical properties when compared to the GAT prism. 22,[25][26][27][28][29] The design differences were described in detail previously. 22 Differences in IOP between the CATS and GAT measurements were strongly correlated with variations in corneal biomechanical properties such as CCT and CH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations